The fragmentary greek tragedy and the myth of Alcmeon - Gambón, Lidia (AADEC - UNL, 2017)
Starting from the vitality that the study of the fragmentary Greek tragedy has acquired in the last decades, the paper emphasizes its value in relation to thesurviving texts of the past, and analyzes the tragic treatment of the myth of Alcmeon. Its profuse presence in the classical drama contrasts, however, with the  fact that no complete work has survived. Despite the scarcity of fragments and the textual and contextual problems posed by this, the lexical survey of Sophoclesand Euripides’ fragmentary plays shows us the fundamental milestones of the Alcmeon’s tragic story and reveals the need for an inquisitive look around thememory of the preserved histories and of those that have been lost.